A Renal Artery Stenting Case: Support for Increased Use of Drug-Eluting Stents - Viertel, Achim; Breese, Nils; Krist, Lars; Groenefeld, Gerian (International Journal of Angiology, 2022)
Fibromuscular dysplasia is a rare, systemic arteriovascular disease that often affects the renal arteries. Balloon angioplasty is recommended for uncontrolled hypertension and compromised renal function; stenting is a bailout option. Drug-eluting stents have been suggested in case reports. We report the successful intervention with an everolimus-coated stent in a very young patient. The patient was followed for 2 years after placing the stent. The success of this case suggests that drug-eluting stents should be used more frequently in comparable situations.
Keywords: renal artery stenosis; fibromuscular dysplasia; duplex ultrasound; percutaneous renal balloon angioplasty; drug-eluting stent; uncontrolled hypertension; antihypertensive therapy